Sequence polymorphism of heat shock protein 70 (HSP70) gene in kelampayan (Neolamarckia cadamba) - Choo, Hui Yik (Universiti Malaysia Sarawak (UNIMAS), 2011)
Neolamarckia cadamba or locally known as kelampayan, is one of the valuable timber tree species. In forest industry, genetic improvement programs based on Single Nucleotide Polymorphisms (SNPs) at the molecular level has become an important tool in the selection of germplasm with desired traits. In this study, DNA sequence of Hsp70 which is gene responsible for heat stress was amplified by polymerase chain reaction (PCR) technique with the specific designed primers based on the cDNA sequence of Hsp70 in N. cadamba. The 527 bp Hsp70 amplicons were subjected to BLASTn analysis to perform the sequence homology search through all known template sequence available in the NCBI. Each sequence was then aligned using CLC Free Workbench 4 software for manual detection of SNPs. A total of ninety SNPs were detected only in the exons of the Hsp70 gene with 12 non-synonymous mutations and 78 synonymous mutations. The sequence of the twelve Hsp70 DNA samples was then subjected to in silico restriction analysis. The exclusiveness of the restriction enzymes BssS1, BstBI, HpyCH4IV, SacI, BsrGI, and Bfa1 obtained for the SNPs at nucleotide 113, 124, 217, 293, 341, and 463 respectively could be useful for genetic markers development.